Travels with Charley in search of America - Steinbeck, John, 1902-1968. (New York : Viking Press, 1962)
Riding in a pickup truck and accompanied by his French poodle, the author sets out on a voyage of rediscovery that takes him through nearly 40 states.
Includes his travels in Maine.
Keywords: Steinbeck, John, -- 1902-1968 -- Travel -- United States; United States -- Description and travel